FosA8-producing E. coli ST131: clinical cases in Italy, February 2023 - Chudejova, Katerina; Caltagirone, Maria Sofia; Mattioni Marchetti, Vittoria; Rezzani, Antonella; Navarra, Antonella; Bitar, Ibrahim (Euro surveillance, 2024)
Fosfomycin-resistant FosA8-producing Enterobacterales are uncommon strains with extremely low incidence in Europe, based on only three reports in the literature. We detected FosA8-producing Escherichia coli ST131 in clinical isolates from two patients admitted in February 2023 to a rehabilitation unit in Italy. The occurrence of rare fosA-like genes in the high-risk clone ST131 is of clinical relevance. The dissemination of FosA-producing E. coli, although still at low levels, should be continuously monitored.
Keywords: Italy; Anti-Bacterial Agents; bakteriální léková rezistence; Drug Resistance, Bacterial; Male; mužské pohlaví; fosfomycin; Microbial Sensitivity Tests; Fosfomycin; Multilocus Sequence Typing; Escherichia coli; ženské pohlaví; Humans; beta-laktamasy; antibakteriální látky; beta-Lactamases; Escherichia coli Infections; Itálie; mikrobiální testy citlivosti; multilokusová sekvenční typizace; Female; lidé; infekce vyvolané Escherichia coli